2018
DOI: 10.3390/md16040115
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Bioactive Marine Meroterpenoids: The Cases of Liphagal and Frondosin B

Abstract: Liphagal and frondosin B are two marine-derived secondary metabolites sharing a very similar polyfused-benzofuran skeleton. The two tetracyclic meroterpenoids were isolated from marine sponges, both featuring a 6-5-7-6 fused ring system. A preliminary bioactive study shows that (+)-liphagal is a selective kinase (PI3K α) inhibitor, while (+)-frondosin B is shown to inhibit the binding of the cytokine interleukin-8 (IL-8) to its receptor, CX-CLR1/2. The unique structures and interesting biological profiles of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“… , As the inhibition of the PI3Kα-mediated biological process leads to the suppression of tumor progression, PI3Kα inhibitors are expected to serve as invaluable sources for developing anticancer agents. Because of its pronounced biological property, liphagal ( 1 ) has gained considerable attention from medicinal and synthetic chemists . In this context, successful efforts have been made independently by the groups of Andersen, , Mehta, George, Alvarez-Manzaneda, Kumar, Stoltz, Katoh, Ferreira, and Wu to chemically synthesize this natural product.…”
Section: Introductionmentioning
confidence: 99%
“… , As the inhibition of the PI3Kα-mediated biological process leads to the suppression of tumor progression, PI3Kα inhibitors are expected to serve as invaluable sources for developing anticancer agents. Because of its pronounced biological property, liphagal ( 1 ) has gained considerable attention from medicinal and synthetic chemists . In this context, successful efforts have been made independently by the groups of Andersen, , Mehta, George, Alvarez-Manzaneda, Kumar, Stoltz, Katoh, Ferreira, and Wu to chemically synthesize this natural product.…”
Section: Introductionmentioning
confidence: 99%
“…This compound inhibited PIK-α (IC 50 = 100 nM), and was also found to be cytotoxic to several tumor cell lines with IC 50 ≈ 1 μM. It has been suggested that 106 has potential application as a new type of kinase inhibitor or even cancer drug [122]. The synthetic route of (+)-liphagal is depicted in Scheme 5, which initiates with (+)-sclareolide (commercially available) and generates the final product in ~10% yield after 13 reaction steps [122].…”
Section: Discussionmentioning
confidence: 99%
“…94 They were isolated from marine sponges and multiple groups have contributed total synthesis studies towards these compounds. 95 The synthesis of liphagal is of particular interest, as it selectively inhibits one isoform of the phosphatidylinositide 3-kinase (PI3K) enzyme family, which is involved in cellular signaling processes. 96 The substrates 5.1.12b,c and 5.1.13c,d can be synthesized in a few steps from commercially available compounds.…”
Section: Special Topic Synthesismentioning
confidence: 99%